Seino van Breugel. 2021. A dictionary of Atong, a Tibeto-Burman language of Northeast India and Bangladesh (Pacific Linguistics 664). Berlin–Boston: De Gruyter Mouton. Pp. xxviii + 378. - Majewicz, Alfred F. (Lingua Posnaniensis, 2022)
REVIEWS: Seino van Breugel. 2021. A dictionary of Atong, a Tibeto-Burman language of Northeast India and Bangladesh (Pacific Linguistics 664). Berlin–Boston: De Gruyter Mouton. Pp. xxviii + 378.